PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS 2 SDN TARIK 1 - Makrifathul Hanik; Ratno Abidin; Titik Kurniawati (Universitas Muhammadiyah Surabaya, 2024)
The aim of this research is to improve student learning outcomes in mathematics subjects with long unit material by applying the problem based learning (PBL) learning model. The method used in this research is a descriptive-quantitative method. The subject of this research were 24 grade 2 students from SD Negeri Tarik 1. Data was taken from pre-test and post-test scores at the beginning and end of learning activities. The results of the comparison of pre-test and post-test scores calculated using the N-gain percentage show that the results are quite effective. The average pre-test score was 50,21 and increased to an average post-test score of 77,50. The N-gain percentage value is 58,31%, which shows that this is quite effectively implemented for learning activities using the problem based learning (PBL) for mathematics subjects in grade 2 of elementary school from SD Negeri Tarik 1